Integrated transcriptome and metabolome analysis reveals a possible mechanism for the regulation of lipid metabolism via vitamin A in rice field eel (Monopterus albus) - Huo, Huanhuan; Hu, Chonghua; Zhou, Qiubai; Xiong, Liufeng; Peng, Mo (Frontiers in Physiology, 2023)
To understand the effects of vitamin A on lipid deposition in rice field eels, integrated liver transcriptome and metabolome were conducted and the changes in the genes and metabolites were assessed. Three groups of rice field eel were fed with 0, 200, and 16 000 IU/kg vitamin A supplementations in their diets for 70 days. The total lipid content in the whole body of the rice field eels was significantly increased with the vitamin A supplementations (p < 0.05). Comparative transcriptome analysis revealed 14 pathways and 46 differentially expressed genes involved in lipid metabolism. Sphingolipid metabolism, glycerolipid metabolism, primary bile acid biosynthesis and steroid hormone biosynthesis were significantly enriched pathways. In these pathways, three differential genes phospholipid phosphatase 1a (PLPP1a), phospholipid phosphatase 2b (PLPP2b), cytochrome P450 21a2 (CYP21a2) were consistent with the change trend of lipid content, and the other three differential genes aldo-keto reductase family 1 member D1 (AKR1D1), uridine diphosphate glucuronic acid transferase 1a1 (UGT1a1), cytochrome P450 1a (CYP1a) were opposite. Metabolomic analysis revealed that primary bile acid biosynthesis, sphingolipid metabolism, steroid hormone biosynthesis and biosynthesis of unsaturated fatty acids were all critical for rice field eel metabolic changes in response to vitamin A. Six important differential metabolites (eicosapentaenoic acid, sphinganine, 11-beta-hydroxyprogesterone, hydroxyeicosatetraenoic acid, cholic acid, and glycochenodeoxycholate) were identified and have provided new insights into how vitamin A regulates lipid deposition. Integrated transcriptome and metabolome analyses revealed that primary bile acid biosynthesis was the only remarkably enriched pathway in both the transcriptome and metabolome while that sphingosine was the main metabolite. Based on the above results, we have concluded that vitamin A promotes lipid deposition in the rice field eel through the primary bile acid synthesis pathway, and lipid deposits are widely stored in cell membranes, mainly in the form of sphingosine. These results will provide reference data to help improve our understanding of how vitamin A regulates lipid metabolism.